Agricultural and Allied Commodities in Indian Foreign Trade: A Compositional Analysis (2009-10 to 2021-22) - Tewari, Poorna Gautam (Journal of Global Economy, Business and Finance, 2026)
The present study has been conducted to examine the exports and imports of agriculture commodities in India during the period from 2009-10 to 2021-22. For this purpose, the Compound Annual Growth Rate (CAGR) of exports and imports of agriculture commodities of Indian Economy has been calculated during the study period. The total exports value of Agriculture and its allied activities in 2009-10 has been Rs.69868.03 Crores, which rose to Rs.276038.55crores in 2021-22 by increasing 8.77 Percent as compared to 2009-10. The agriculture and allied imports in 2009-10 have been Rs.43490 Crores, which decreased to Rs.209350Crores in 2021-22 by slightly increased by 4.57Percent compared to 2009-10 in which it was 3.18 Percent. The study found that the CAGR of Exports of agriculture & allied products is 0.11 and, it is 0.12 in case of Imports of agriculture & allied products during the study period. The balance of trade in agriculture has favorably increased during the study period from Rs.26378 Crore to Rs.66689 Crore during the same period in 2021-22. On the basis of findings, the study recommended to the government of India that there is need of a viable agriculture export policy, which will follow farmer’s centric approach. This approach will ensure food security in India and, also maintain a friendly environment for flourishing Indian agricultural exports at global level.